Considerations and ambivalence about the tosco aesthetic - Batista, Gabriel Silva (2023)
The adjective ‘tosco’ is present in Portuguese language carrying a deliberately negative connotation, qualifying things as gross, rude, cringeworthy, among other definitions. This article has the objective of observing how these attributes are used for an aesthetic qualification of diverse visuals, weaving relations between image, viewer and contemporary world. Using considerations about similar aesthetics, like the grotesque, it intends to investigate how an aesthetic category named as tosca would be delimited, and how visual expressions derived from it would be constructed. Also, on the basis of examples from contemporary art, it will investigate the subversive potencies of an aesthetic constructed inside these lines, considering the effects that a proposition of visual relation would have over subjectivity.